Dendrophthoe pentandra methanolic leaf extract increases progesterone levels in female rats - Lazuardi Mochamad; Bambang Hermanto (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUNDHuman infertiliy cases in Indonesia have tended to increase at about 2-5%annually since 2000. Many tropical plants in Indonesia are potential sources of novel anti-infertility compounds, e.g. Dendrophthoe pentandra L. Miq. (benalu duku), a parasitic plant growing on Lansium domesticum. The objective of this study was to identify the effect of crude methanolic Dendrophthoe pentandra leaf extract on follicle stimulating hormone (FSH) and progesterone levels in female rats.METHODSFourteen Rattus norvegicus Wistar strain female rats were divided into anintervention group and a control group, and synchronized to estrus via thepheromone synchronizing method. The intervention group was given daily single intramuscular injections of crude methanolic Dendrophthoe pentandra leaf extract at 100 mg/kgBW for 4 days, while the control group was given daily single intramuscular injections of 1 mL of distilled water. Determination of FSH and progesterone levels in whole blood was done using the Randox Evidence Investigator analyzer. The data were subjected to the t test for two independent samples.RESULTSMean FSH in the intervention group was 9.28 ± 6.72 mIU/mL, which was lower than mean FSH of 24.80 ±16.35 mIU/mL in controls (p<0.05). Mean progesterone level in the intervention group was 33.55±13.96 nmol/L, twice as high as that in the control group, which was 18.47± 06.47 nmol/L (p<0.05).CONCLUSIONSCrude methanolic Dendrophthoe pentandra leaf extract reduces FSH andincreases progesterone levels in female rats, but cannot yet be recommended for use as fertility hormone inhibitor or stimulator in rats.